CPA Experience Requirements and Service Quality: Experience from the US - Jack Armitage; Shane Moriarity (STIE Malangkucecwara, 2020)
This study examines the requirement of obtaining prior practical experience toobtain a license to provide professional assurance services. Disciplinary sanctionsimposed by the American institute of certified public accountants (AICPA) is used tocompare differing state experience requirements required for licensing. The study usesthe per capita number of sanctions for substandard professional service as a proxy forthe quality of professional service being provided in each state. The results revealedconsistent associations between the length of minimum state experience requirementsfor licensure and the proxy. While the results suggest that experience provides societywith a benefit, the results do not quantify it and the justification for adopting a specificexperience requirement still requires a judgmental assessment of the trade-off betweenthe costs that the requirement imposes and the benefits it will bestow